Identification Of Chlorine Content In Mantao Bread Sold In The City Of Parepare - Bunyanis, Fitriana; Lidiawati, Dewi; Hawasiah, Hawasiah (Universitas STRADA Indonesia, 2021)
Background: Mantao bread is a typical Parepare culinary delicacy that is much in demand and sought after by the public when visiting Parepare. However, in making mantao bread, sometimes the producers add a dangerous additive, namely chlorine. Chlorine is a chemical used by consumers that can have harmful effects on consumers. Purpose: This study aimed to determine the chlorine content and to analyze the chlorine content of the bread sold in the city of Parepare. Method: using two methods, namely color test and deposition test. Results: there was no color change when tested and the results of the precipitation test showed no sediment. Conclusions: mantao bread sold in the city of Parepare does not contain chlorine